La institucionalización del País Vasco norte - Eguzki Urteaga (Revista Vasca de Administración Pública, 2017)
Since 1 January 2017, the ten Public Bodies for Intermunicipal cooperation have been merged to constitute an Agglomeration Community of the Northern Basque Country, endowing that territory with a representative institution. This creation is after all the result of a long historical process of wars, revolutions, changes of regime and mobilizations both by local elected representatives, economical sectors, political movements as well as by civil society organizations. That is why it seems useful to keep in mind the precedents of this institutionalization process and make it clear the effective institutionalization of that territory with its actors, claims, triggers and features. It would also be worth considering, looking to the future, the challenges this institution will have to face in the years to come. These latter refer both to the powers, governance and funding of the new entity; not omitting the embodiment and articulation of the territory, its propensity to become the reference for certain matters as well as its capacity to transform itself into a Territorial authority with a particular status.